Assessment of potential drug-drug interactions and its associated factors in the hospitalized cardiac patients - Ghulam Murtaza; Muhammad Yasir Ghani Khan; Saira Azhar; Shujaat Ali Khan; Tahir M. Khan (Elsevier, 2016)
Drug-drug interactions (DDIs) may result in the alteration of therapeutic response. Sometimes they may increase the untoward effects of many drugs. Hospitalized cardiac patients need more attention regarding drug-drug interactions due to complexity of their disease and therapeutic regimen. This research was performed to find out types, prevalence and association between various predictors of potential drug-drug interactions (pDDIs) in the Department of Cardiology and to report common interactions. This study was performed in the hospitalized cardiac patients at Ayub Teaching Hospital, Abbottabad, Pakistan. Patient charts of 2342 patients were assessed for pDDIs using Micromedex® Drug Information. Logistic regression was applied to find predictors of pDDIs. The main outcome measure in the study was the association of the potential drug-drug interactions with various factors such as age, gender, polypharmacy, and hospital stay of the patients. We identified 53 interacting-combinations that were present in total 5109 pDDIs with median number of 02 pDDIs per patient. Overall, 91.6% patients had at least one pDDI; 86.3% were having at least one major pDDI, and 84.5% patients had at least one moderate pDDI. Among 5109 identified pDDIs, most were of moderate (55%) or major severity (45%); established (24.2%), theoretical (18.8%) or probable (57%) type of scientific evidence. Top 10 common pDDIs included 3 major and 7 moderate interactions. Results obtained by multivariate logistic regression revealed a significant association of the occurrence of pDDIs in patient with age of 60 years or more (p < 0.001), hospital stay of 7 days or longer (p < 0.001) and taking 7 or more drugs (p < 0.001). We found a high prevalence for pDDIs in the Department of Cardiology, most of which were of moderate severity. Older patients, patients with longer hospital stay and with elevated number of prescribed drugs were at higher risk of pDDIs.